Use of Assisted Reproduction Techniques in Male Pathologies: Molecule Based Sperm Selection Methods - Marini, Patricia Estela (2017)
Infertility is a widespread problem that is found in over 15% of couples. In 50 % of the cases, the male factor is the key. In order to improve pregnancy rates in assisted reproductive techniques (ART), new methods to select sperm subpopulations are required. These methods are under constant evaluation, and their possible genetic and epigenetic effects on the offspring must be considered. New concepts such as DNA fragmentation and sperm apoptosis are being introduced in andrology and are considered to develop new techniques. Recently, molecule-based methods have been developed for the purpose of overcoming deficiencies in classical selection methods that involve sperm morphology and movement. One of these methods is physiologic intracytoplasmic sperm injection (PICSI), which selects spermatozoa through their property to bind to hyaluronic acid, a component of the cell-oocyte complexes that acts as a natural selector of spermatozoa. But the top rated method is based on the property of the protein annex in A5 (ANXA V) to bind to phosphatidylserine (PS), a marker of apoptosis. Magnetic-Activated Cell Sorting (MACS) conjugated with ANXA V (MACS-ANXA V) is used to remove apoptotic sperm with exposed PS from a semen sample. The use of MACS-ANX V seems to produce good quality sperm when it is evaluated by in vitro assays. But when MACS-ANXA V is used previous to ART, controversies persist regarding the benefits of sperm selection in reproductive outcomes. In this review, we consider the use of MACS-ANXA V, particularly in cases of male pathologies.